Relationsadjektive im Deutschen, Französischen und Russischen - Mravlag, Hedwig (Studien des Interdisziplinären Frankreich-Schwerpunkts der Universität Innsbruck, 2013)
In the classification of adjectives numerous variants are possible. A rough classification into lexical-semantic point of view, the distinction of quality and Relations adjectives. Both in German and in French and Russian, this differentiation seems to have some significance, as many grammars to refer to them. Due to language-specific differences, it is in the analysis of relational adjectives in different languages particularly interesting to look at those alternative designs, with which relations adjectives in the source text for a translation or interpretation to be replaced.